Adolfo N. Dacanáy, SJ. The Sacraments of Initiation (Baptism, Confirmation, Eucharist): A Commentary on Cc. 849–958 of the Code of Canon Law. Pasig: Anvil Publishing, Inc., 2006. 204 pages. - Badion, Justin Joseph G. (Archīum Ateneo, 2016)
Excerpt: Written in 2006 as the second volume in a planned four-volume work on the sacramental law of the Church, The Sacraments of Initiation (Baptism, Confirmation, Eucharist): A Commentary on Cc. 849–958 of the Code of Canon Law proves to be an excellently crafted resource for all who wish to be knowledgeable in the canon law underlying the various sacraments of initiation of the Church. Continuing the tradition of excellent scholarship that was begun in 2000 with the publication of Canon Law on Marriage: Introductory Notes and Comments, Dacanáy elaborates on previous interpretations, as well as the prescribed interpretation of the canon law, including this time matters concerning the three sacraments of initiation.